2018
DOI: 10.1097/gox.0000000000001834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Keller Funnel on the Rate of Capsular Contracture in Periareolar Breast Augmentation

Abstract: Background:Capsular contracture is 1 of the most common complications after breast implant surgery and is a major indication for reoperation. Capsular contracture is believed to be a multifactorial process that is affected by implant texture, incision type, and ultimately pocket contamination. This contamination causes a biofilm that leads to capsular contracture. The intraoperative use of a Keller funnel is a mechanical way to decrease the implant’s contact with the skin and ducts, reducing bacterial contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…12 Funnel use has also been shown to reduce capsular contracture. 24 With these advantages, funnels have been used considerably in cosmetic breast surgery. Funnels can also be effectively used in implant breast reconstruction, as confirmed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…12 Funnel use has also been shown to reduce capsular contracture. 24 With these advantages, funnels have been used considerably in cosmetic breast surgery. Funnels can also be effectively used in implant breast reconstruction, as confirmed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We have already extensively studied and published on infection control in breast tissue. 32 , 33 Of course, the breast case becomes inherently colonized over the course of the surgical procedure; however, the sources of the infectious agents are the nipple ducts and axilla, not the instruments. We have found no evidence in the literature to suggest that changing instruments leads to a decrease in surgical site infection rates.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that an implant-based augmentation mammaplasty via a periareolar incision produces a higher rate of CC. 20 , 21 Moreover, some “Core” studies have shown that the rate of CC was significantly higher in secondary cases than in primary ones. 6 , 12 , 22 , 23 Furthermore, the use of anatomical implants was closely associated with a decreased rate of CC.…”
Section: Methodsmentioning
confidence: 99%